Tracking control for planar nonminimum-phase bilinear control system with disturbance using backstepping - Khozin Mu`tamar; Janson Naiborhu; Roberd Saragih; Dewi Handayani (Institute of Advanced Engineering and Science, 2022)
This article presents the design control of a tracking problem for a non-minimum phase bilinear control system containing disturbance. The bilinear control system is assumed to have a relative degree one and non-minimum phase, which means it has unstable internal dynamics. The disturbance exists only in state variables corresponding to the control function in external dynamics. The control design was carried out using the backstepping method, which was applied to the normal form of the bilinear control system. Internal dynamics will be stabilised using virtual control to overcome unstable internal dynamics. The last step will stabilise the external dynamics and disturbance using the original control function. The simulation results show that the proposed control method can rapidly drive the output to the given trajectory. Control performance varies depending on the control parameter setting. The higher the control parameter, the better the control performance, evaluated using integral absolute error.